The Nigerian Language/ Religion and Culture: Tools for Peaceful Co-Existence in the South-Western Nigeria - Iyabode, Ajibade Mufuliat; Bukola, Johnson Comfort; Atolagbe, Issah Jimoh (European Scientific Journal, ESJ, 2023)
Nigeria and the world at large has experienced series of conflicts which have led to killing of innocent citizens and wanton destruction of valuable properties. Despite all efforts made at proffering solutions to conflicts and violence, Nigeria is yet to achieve the intended resolution, hence, the desirability of this study. The aim of this study therefore, is to investigate the use of language, religion and culture in generating a peaceful co-existence among the people of the south-western Nigeria. The study was based on social exclusion theory and adopted a survey research design. A structured questionnaire was used to collect data from a total of 180 respondents. Data were analyzed with the use of descriptive statistics. It is expected that the study will help Nigerians at large on how best to resolve their internal conflict through the appropriate use of language, culture and religion.